Super-Flexibility for Knowledge Enterprises A Toolkit for Dynamic Adaptation - Bahrami, Homa. (Springer Berlin Heidelberg, 2010)
Today, we live in a dynamic and inter-connected world. A multitude of "revision triggers" make it necessary to anticipate, prepare for, and continuously adapt to new realities. The key to dynamic adaptation we argue, is to become "super-flexible". Super-flexibility is defined as the ability to engage in a continuous balancing act: on the one hand, we need to withstand turbulence and create stable anchors, on the other hand, we have to transform and adapt to new realities. Our leadership "toolkit" should help us diagnose on the fly, and take rapid actions as new developments unfold. This book is about how business leaders can harness uncertainty and make their teams and enterprises "super-flexible". Based on 25 years of field research, advisory work, and professional experience in Silicon Valley' s innovative ecosystem, the authors present a cross-functional, "general management" toolkit for strategizing, organizing, leading, and ultimately re-inventing knowledge enterprises for a dynamic world.